Examining the role of wine brand love on brand loyalty: a multi-country comparison - Drennan, J. (2015)
This study develops and tests a model through a multi-country study that considers consumer wine knowledge and wine experience, wine brand trust and wine brand satisfaction as antecedents of wine brand love, and wine brand loyalty as a consequence of wine brand love. Data were collected in five wine-producing countries (Australia, Chile, France, Mexico and Portugal) with a final sample of 3462 completed surveys. Hypotheses were tested with structural equation modeling and the findings confirm the importance of brand love as both a mediator and direct influence on brand loyalty for wine consumers. Furthermore, brand satisfaction was positively and significantly related to brand love. In addition, wine experience, rather than wine knowledge, positively influenced brand trust and satisfaction. Finally, results also identify differences between countries thereby providing insights into how companies should focus their marketing strategies internationally.